CGIAR System Annual Performance Report 2019: Summarized Report - CGIAR System Organization (CGIAR System Organization, 2020)
In 2019, poverty, hunger and malnutrition continued to be a daily reality for millions as the final decade approached to meet the United Nations Sustainable Development Goals (SDGs). Action was lagging on climate change, even as the effects of extreme weather and increased disaster events became harder to ignore. And as the year drew to a close, the first cases were recorded of COVID-19, a disease that within months would take a severe toll on human health, and upend the global economy. At the center of these combined crises was one common factor. Food – the way we grow, catch, transport, process, trade and consume it – is central to the main challenges facing humanity. As the world’s largest global agricultural innovation network, CGIAR has a crucial role to play in transforming food systems in a climate crisis. In 2019, CGIAR’s research and innovations contributed and provided solutions to the complex challenges related to food security, environmental protection and sustainability, and the protection of health and livelihoods. With its key focus on agricultural research for development (AR4D), CGIAR conducts research that leads to positive development impacts and public goods that benefit those in need. In 2019, CGIAR delivered measurable advances toward meeting the SLOs and SDGs. The CGIAR Portfolio – driven by the combined efforts of CGIAR Research Centers and grouped into challenge-led research clusters – presented 97 cases of high-level, long-term, at-scale impact for sustainable development. A total of 150 Outcome Impact Case Reports (OICRs) – short reports on the impact of CGIAR research – were also reported. A total of 888 innovations – significant products or findings – were reported in 2019, similar to the number reported in 2018. Important capacity development contributions were also made in 2019. A total of 796,273 trainees (including long– and short– term; 54% men and 46% women) were involved across the CGIAR Portfolio. A total of 538 PhD students were incorporated in CGIAR research intiatives in 2019, 49% (265) of them women.